SALING BEREBUT TUHAN; PANDANGAN BASSAM TIBI TENTANG FUNDAMENTALISME - Nasiruddin Nasiruddin (Universitas Yudharta Pasuruan, 2017)
Islamic fundamentalism is not only a problem for non-Muslims but also for Muslims, as evidenced by the emergence of many pros and cons against this phenomenon. Islamic fundamentalism is just one type of a new global phenomenon in world politics. This movement represents a political ideology, not a religion as a culture, and even trapped in the trap of clash between civilizations in a socio-political context. Therefore, for Bassam it is important to distinguish between Islam as a religion and civilization and Islam as a political ideology ( Fundamentalism). Then Bassam Tibi insists that fundamentalism is not a spiritual belief but as a political ideology based on religious politicization for socio-political and economic purposes. There are several teachings of Islamic fundamentalism more a manifestation of a collection of political theories than religious theology and practice. They have made Islam a political ideology. As the religion of Islam is drawn into the political area by formulating the legality of Islam (syari'at Islam), realizing it, and building an Islamic system and then maintaining it in such a way in the life of the nation and state. According to Bassam Tibi, Islam as a political ideology is actually something new in Islam. For him, there is no legal basis in the Qur'an and al-Hadith which expressly enjoined the politicization of Islam developed by the fundamentalist movement. Bassam Tibi added that the word hukumah (government) or daulah (state) does not exist in the Qur'an and Hadith. Thus, this is a new interpretation of Islam, or a new phenomenon recently discovered in modern times.